A Descriptive Study of First Trimester Pregnant Women's Knowledge of Nausea and Vomiting - Sulistyo Rahmawati, Maria; Sumantri, Sumantri; Sri Mualti, Triwik (Jurnal Kebidanan dan Kesehatan Tradisional, 2024)
Background: Pregnancy causes various physiological changes in women, one of which is hormonal changes that often cause discomfort in the form of nausea and vomiting in the first trimester. If not treated immediately, this condition can lead to fluid loss, fetal growth and development disorders, and even the risk of maternal death. This study aims to determine the level of knowledge of pregnant women in their first trimester about nausea and vomiting at the Bayat Community Health Center in Klaten Regency.  Methods: This study used a quantitative descriptive design with total sampling technique. The population consisted of all pregnant women in their first trimester who visited the Bayat Community Health Center in October 2022, totaling 60 respondents. The research instrument used a structured questionnaire, and the data were analyzed using frequency distribution.  Results: The results showed that most respondents were aged 20–35 years, had a high school education, worked as housewives, had received information about nausea and vomiting from midwives, and had two to four children. The level of knowledge of pregnant women in their first trimester was classified as good in terms of understanding, signs and symptoms, causes, prevention, and the effects of nausea and vomiting.  Conclusion: The knowledge of pregnant women in their first trimester at the Bayat Community Health Center in Klaten Regency about nausea and vomiting was in the good category. It is recommended that health workers, especially midwives, continue to improve education and counseling for pregnant women in their first trimester regarding the prevention and treatment of nausea and vomiting to reduce the risk of pregnancy complications.